(untitled) (Communications in Computational Physics, 2010)
Natural cavitation is defined as the phenomenon of the formation of vapor bubbles in a flow due to the pressure falls below the liquid's vapor pressure. The inception of the cavitation bubble is influenced by many factors, such as impurities, turbulence, liquid thermal properties etc. In this paper, we simulate a 2D cavitation "bubble" growth under shear flow in the inception stage by Single-Component-Multiphase Lattice Boltzmann Model (SCMP LBM). An empirical boundary condition sensitive 2D bubble growth rate, R ∼ et , is postulated. Furthermore, the comparison is conducted for bubble behavior under different shear rates. The results show that the cavitation bubble deformation is coincident with prior droplet theories and the bubble growth decreases slightly with the flow shear rate.